(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Spices are the elements that give food its taste. Food’s fragrance, texture, and color are its main purposes. They also serve as a preservative, as well as providing nutritional and physiological advantages. Cumin (Cuminum cyminum) is a blooming plant in the Apiaceae family that is locally known as "zeera." Many eastern cuisines call for it as a condiment and seasoning. Cumin is well-known for its anti-oxidant properties. Seed spices affect a number of biological systems, such as the digestive, circulatory, reproductive, or neurological systems, causing a range of metabolic but also physiologic consequences. Antioxidants, antidiabetic, anticancer, antimicrobial activity, hypolipidemic influence, insecticidal, beneficial in heavy menstrual bleeding, aiding digestion, high blood pressure, instrumentation of enzymes involved, immune function, reduction of inflammatory process, molecular mechanism, modulations of immune systems, The purpose of this research is to have a thorough analysis on the present trends in research here on health advantages of four common seed seasonings: cumin, coriander, but also fennel.